Effect of acute dietary nitrate consumption on oxygen consumption during submaximal exercise in hypobaric hypoxia - Carriker, C. R.; Mermier, C. M.; VanDusseldorp, T. A.; Johnson, K. E.; Beltz, N. M.; Vaughan, R. A.; McCormick, J. J.; Cole, N. H.; Witt, C. C.; Gibson, A. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Reduced partial pressure of oxygen impairs exercise performance at altitude. Acute nitrate supplementation, at sea level, may reduce oxygen cost during submaximal exercise in hypobaric hypoxia. Therefore, we investigated the metabolic response during exercise at altitude following acute nitrate consumption. Ten well-trained (61.0 ± 7.4 ml/kg/min) males (age 28 ± 7 yr) completed 3 experimental trials (T1, T2, T3). T1 included baseline demographics, a maximal aerobic capacity test (VO2max) and five submaximal intensity cycling determination bouts at an elevation of 1600 m. A 4-day dietary washout, minimizing consumption of nitrate-rich foods, preceded T2 and T3. In a randomized, double-blind, placebo-controlled, crossover fashion, subjects consumed either a nitrate-depleted beetroot juice (PL) or ~12.8 mmol nitrate rich (NR) beverage 2.5 hr before T2 and T3. Exercise at 3500 m (T2 and T3) via hypobaric hypoxia consisted of a 5-min warm-up (25% of normobaric (VO2max) and four 5-min cycling bouts (40, 50, 60, 70% of normobaric VO2max) each separated by a 4-min rest period. Cycling RPM and watts for each submaximal bout during T2 and T3 were determined during T1. Preexercise plasma nitrite was elevated following NR consumption compared with PL (1.4 ± 1.2 and 0.7 ± 0.3 uM respectively; p < .05). There was no difference in oxygen consumption (-0.5 ± 1.8, 0.1 ± 1.7, 0.7 ± 2.1, and 1.0 ± 3.0 ml/kg/min) at any intensity (40, 50, 60, 70% of VO2max), respectively) between NR and PL. Further, respiratory exchange ratio, oxygen saturation, heart rate and rating of perceived exertion were not different at any submaximal intensity between NR and PL either. Blood lactate, however, was reduced following NR consumption compared with PL at 40 and 60% of VO2max (p < .0.05). Our findings suggest that acute nitrate supplementation before exercise at 3500 m does not reduce oxygen cost but may reduce blood lactate accumulation at lower intensity workloads.